2000
DOI: 10.1128/aem.66.4.1360-1368.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization, Controlled Overexpression, and Inactivation of the Major Tributyrin Esterase Gene of Lactococcus lactis

Abstract: The gene encoding the major intracellular tributyrin esterase of Lactococcus lactis was cloned using degenerate DNA probes based on 19 known N-terminal amino acid residues of the purified enzyme. The gene, named estA, was sequenced and found to encode a protein of 258 amino acid residues. The transcription start site was mapped 233 nucleotides upstream of the start codon, and a canonical promoter sequence was identified. The deduced amino acid sequence of the estA product contained the typical GXSXG motif foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 51 publications
7
70
0
Order By: Relevance
“…In the central section, Ser156 of C. boidinii is in the consensus sequence GXSXG around the catalytic serine, typical of all lipases and esterases (Fernandez et al, 2000). Near the C-terminus, conserved His273 is found, which is predicted to be the catalytic histidine residue (Cygler et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In the central section, Ser156 of C. boidinii is in the consensus sequence GXSXG around the catalytic serine, typical of all lipases and esterases (Fernandez et al, 2000). Near the C-terminus, conserved His273 is found, which is predicted to be the catalytic histidine residue (Cygler et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…EstA is probably a key enzyme in the development of food flavor through the degradation of esters and lipids and the synthesis of esters and thioesters (38). Studies using an EstAnegative mutant partially confirmed this (12). EstA has an optimal temperature of 30°C and exhibits maximal activity at pH 7.5 with p-nitrophenyl (pNP) esters having acyl chains that are four to six carbon atoms long.…”
mentioning
confidence: 72%
“…EstA has an optimal temperature of 30°C and exhibits maximal activity at pH 7.5 with p-nitrophenyl (pNP) esters having acyl chains that are four to six carbon atoms long. This enzyme exhibits sequence homology to S-formyl glutathionine hydrolase, which can explain its thioesterase activity (12). EstA belongs to a superfamily of phylogenetically related proteins with representatives in the domains Eukarya, Bacteria, and Archaea (18,20,24,31).…”
mentioning
confidence: 99%
“…The enzyme activity of the EstE7 proteins in various oligomeric states was measured using p-nitrophenyl butyrate. 12 The esterase activity was measured by spectrophotometric assay at pH 7.5 and 30 o C for 5 min using 5 mM p-nitrophenyl butyrate as the substrate. Larger aggregates (void volume in size exclusion chromatography), aggregated, dimer and monomer EstE7 proteins were concentrated to 3 mg/mL and then used for subsequent analyses.…”
Section: Introductionmentioning
confidence: 99%